CYSTIC ENDOMETRIAL HYPERPLASIA - OPEN PYOMETRA COMPLEX IN A FEMALE PUG - HAJI, M M; BORPUJARI, D; TALUKDAR, D J; AHMED, F A; LALRINTLUANGA, K; SARMA, K (The Indian Journal of Animal Reproduction, 2017)
A five-year old pug had the history of inappetance, polydipsia, occasional vomition and diarrhea. The vaginal examination revealed brown chocolate malodorous discharge. The uterine ultrasound showed hyperplasia and multiple distended circular hypoechoic and anechoic cysts filled with echogenic material in the uterine wall along with distended uterine horns containing large volume of cellular contents. Based upon ultrasonography, vaginal cytology and haemato-biochemcial picture, the animal was diagnosed with cystic endometrial hyperplasia (CEH)- open pyometra complex. The bitch was treated with synthetic prostaglandin analog, methyl ergometrine and ceftriaxone. After one week, the bitch showed marked improvement with the absence of vaginal discharge, normal ultrasonographic report of uterus and normal haemato-biochemical picture. In conclusion, a synthetic prostaglandin analog along with methyl ergometrine can be used as the drug of choice for treating CEH-open pyometra complex without any adverse effect.